Margaret Mead. shaping a new world. - Moss, Allyn (Encyclopaedia Britannica Press New York, 1963)
When Margaret Mead was a little girl, she moved about a good deal with her scholar family, meeting new and different people.
Keywords: Mead, Margaret -- 1901-1978; Margaret Mead